Community Empowerment of Ponoragan Village, Loa Kulu District Through Education and Composing with The Takakura Method - Muhamad Dedy H; M. Alviansyah; Hansen Hansen (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Garbage is an object or material that is no longer used by humans so it is thrown away. The societal stigma regarding waste is that all garbage is disgusting, dirty, etc., so it must be burned or disposed of properly. All community activities always generate waste. Takakura is a household-scale composting method using the "Takakura Basket" which was introduced by Koji Takakura, a waste expert from Japan.  The method for determining problem priority was the Capability, Accessibility, Readiness, and Leverage (CARL) method. Training on making Takakura baskets on Thursday, December 13, 2021, at 08.00 WITA at the Melati Putih Posyandu, Ponoragan Village, Loa Kulu District. This activity was attended by 24 participants. Wilcoxon test results show that the significant value is (0.000). This value has a value smaller than the alpha value (0.05). The interpretation obtained is that there is an increase in respondents' knowledge. The results related to counseling on making Takakura baskets are in line with those carried out by (Rozikin et al., 2019). Field Learning Practice Activities (PBL) Students of the Muhammadiyah University of East Kalimantan conducting training and education by making compost using the Takakura method succeeded in providing knowledge to the people of Ponoragan Village RT 06.